2012
DOI: 10.1088/0957-4484/23/41/415604
|View full text |Cite
|
Sign up to set email alerts
|

Spark erosion: a high production rate method for producing Bi0.5Sb1.5Te3nanoparticles with enhanced thermoelectric performance

Abstract: We report a new 'spark erosion' technique for producing high-quality thermoelectric nanoparticles at a remarkably high rate and with enhanced thermoelectric properties. The technique was utilized to synthesize p-type Bi(0.5)Sb(1.5)Te(3) nanoparticles with a production rate as high as 135 g h(-1), using a relatively small laboratory apparatus and low energy consumption. The compacted nanocomposite samples made from these nanoparticles exhibit a well-defined, 20-50 nm size nanograin microstructure, and show an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 38 publications
0
37
0
7
Order By: Relevance
“…40 The spark erosion process was originally invented by Berkowitz and Walter to produce micron-sized and amorphous powders of metals. 41 By tuning the process conditions, Nguyen et al have demonstrated the application of the spark erosion process in producing large quantity (>100 g scale) of metal and semiconductor nanoparticles.…”
Section: Spark Erosionmentioning
confidence: 99%
See 3 more Smart Citations
“…40 The spark erosion process was originally invented by Berkowitz and Walter to produce micron-sized and amorphous powders of metals. 41 By tuning the process conditions, Nguyen et al have demonstrated the application of the spark erosion process in producing large quantity (>100 g scale) of metal and semiconductor nanoparticles.…”
Section: Spark Erosionmentioning
confidence: 99%
“…41 By tuning the process conditions, Nguyen et al have demonstrated the application of the spark erosion process in producing large quantity (>100 g scale) of metal and semiconductor nanoparticles. 40 The basic idea and apparatus of the spark erosion process is shown in Fig. 6, which is a sketch of the spark erosion system.…”
Section: Spark Erosionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these technologies are still far from commercialization in terms of mass production. The continuous attempts to reduce grain size of the TE materials have been tried via high-energy ball milling [15,16], spark erosion [17], melt spinning (MS) [8,[18][19][20], and bottom-up chemical synthesis processes [21][22][23].…”
Section: Introductionmentioning
confidence: 99%